ANALISIS KOMPARATIP HASIL UN SMP TAHUN 2011 DAN 2012 KABUPATEN KLATEN - ., Gunarto (MAGISTRA, 2012)
Gunarto, teacher, The Comperative Analysis of Junior High School National Examination Result At The Year 2011 and 2012 in Klaten Regency. This research is a qualitative descriptive research which based on the National Examination (UN) result document for the Junior High School (SMP) at the year 2011 and 2012 which is published by the information center and the national examination estimation in Jakarta. Collecting of the other data likes , the task documents , the result of the Final Mark (NA) can be found from the technical official functionary of the education dines service in Klaten Regency and the accomplishment partners of National Examination directly when the examination happened by the researcher. The preparation of the data using the qualitative analysis which used triangulation method, includes the data source , the result of data, and taking over the judgement. All of the components are chosed the most valid one by reductioning the data. The purpose of this research is giving the understanding to the common community and teachers about the result of the National Examination for the Junior High School (UN SMP) at the year 2011 and 2012 in Klaten Regency and the position at Surakarta Residency and at Central Java Province , and alsoto know the achievement of study according to KTSP. The result of this research shows that the National Examination for the junior high school in Klaten Regency the achievement has been decreasing, it can be seen from the average of the fourth (4) lessons, that is in the early it gets 6,90 at the year of 2011 becomes 6,65 at the year 2012. If we see them from each lessons,the increasing one is the Indonesian lesson that gets 7,30 at the year of 2011 becomes 8,25 at the year 2012. And according to the dimension of KTSP for the Indonesian lesson it can be said that it is achieved, whereas for the fourth (4) lessons eventhough the average mark can reach 6,65 it cannot be said that they are achieved because they have less mark than 75% from the amount of students who joined the National Examination get the average mark at the point of 6,65. KTSP wants 75% classically passed so it can be said that it is achieved, but if it is seen from each lesson ,so the Indonesian can be said that it is achieved. The conclusion, the participants of National Examination at the year 2012 in Klaten Regency has decreasing at about 0,25. Eventhough the rank at the residency is permanent that is at the third (3) position from the seventh (7) regencies/cities, but at the central java province decreasing to the fifteenth (15) rank which it was at the thirteenth (13) position before from the thirty five (35) regencies/cities. That is why the achievement of study according to KTSP has not been achieved yet. Key word : National Examination and Achievement of Study